2012
DOI: 10.1080/01932691.2011.567154
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Microemulsions Formulated with Sodium Alkyl Polypropylene Oxide Sulfate and a Cationic Hydrotrope

Abstract: The partial ternary phase diagram of anionic extended surfactant of alkyl polypropylene oxide sulfate C 12 (PO) 4 SO 4 alone and combined with the cationic hydrotrope, tetrabutyl ammonium bromide with water and decane were determined under ambient conditions. Middle phase microemulsion was formulated using salinity scans in the dilute region of surfactant/brine/decane. Visual inspection as well as cross polarizer and optical microscopy were used to detect anisotropy. Spinning drop tensiometer was used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…There are few cationic hydrotropes known, 1 and only in the past few years some sparse studies using quaternary ammonium-based salts were reported. [70][71][72] In summary, the results obtained here clearly support that ILs may constitute a novel series of cationic hydrotropes. Effect of the cation alkyl side chain length 1) and all the compounds have a similar impact on the solubility irrespective of their alkyl side chain lengths.…”
Section: Effect Of the Ionic Liquid Cationsupporting
confidence: 68%
“…There are few cationic hydrotropes known, 1 and only in the past few years some sparse studies using quaternary ammonium-based salts were reported. [70][71][72] In summary, the results obtained here clearly support that ILs may constitute a novel series of cationic hydrotropes. Effect of the cation alkyl side chain length 1) and all the compounds have a similar impact on the solubility irrespective of their alkyl side chain lengths.…”
Section: Effect Of the Ionic Liquid Cationsupporting
confidence: 68%
“…[18] Earlier, we showed that the presence of the cationic hydrotrope, tetra butyl ammonium bromide (TBAB) had completely eliminated the formation of liquid crystal from the ternary phase diagram of C 12-13 PO 4 SO 4 Na, water and decane. [19] Therefore, in the present study we used TBAB in most of the work and compared it with another cationic hydrotrope, Variquat cc-9 NS which is a poly propylene oxide ammonium bromide.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the γ interface at the oil/water interface without a surfactant is . Surfactants lower the γ interface significantly to for ionic surfactants and to for nonionic surfactants. These values also correspond to the maximum mutual solubility between the oil and water phases. ,, Therefore, significant increases in the interfacial area occur to balance the low interfacial tension and control the formation of μEs. Underlying these changes in the interfacial area are changes in surfactant packing and any transport processes that are connected to it.…”
Section: Introductionmentioning
confidence: 99%